(untitled) (Journal of Educational Sciences, 2021)
This article analyzes the topical problems in the training methods in swimming to identify lack of peer-reviewed literature on methodology of training. The review is based on the research of different areas of swimming theory and methodology, biomechanics, physiology; the structure and content of individual technologies. The aim of this study: the method of high-intensity ultra-short race pace training method, developed by the American coach and scientist Brent Rushall. In the world community of swimming coaches in reserve training generally accepted training methods authored by Soviet Union scientists are actively used. However, modern coaches pay little attention to planning and develop the special physical qualities of swimmers on the basis of medical and biological processes. Optimization of swimmers’ training methods is often discussed in the scientific literature. The narrow specificity of the sport implies that adaptation to training loads depends largely on the type of training. Therefore, the training methods should be based on the system of energy supply, technical skills and the range of motor qualities demanded by the specificity of the sport. The proposed study presents an analysis of the modern method of developing special physical qualities based on the laws of bioenergetics. Key words: swimming, bioenergy, low-volume high-intensity training.